Rachel de Queiroz cronista: um exame de aspectos literários e lingüísticos de sua "Última Página" em O Cruzeiro - Silva, Ana Roza da (2007)
This paper aims to comprove the personality of the talented chronicler, Rachel de Queiroz. The focus of the study is the stylistic dimension of the chronicles published in the section Última Página, of the magazine O Cruzeiro, in 1940 at 1970. Her style is based on exploration of the linguistics standards like colloquiality, some grammatical categories of the textual functions, the metalinguistic function and the parenthesis s discursive-textual functions.